KESIAPAN GURU GEOGRAFI DALAM IMPLEMENTAS KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI SMA SUMATERA BARAT - Dia Saputri; Bigharta Bekti Susetyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Merdeka Curriculum requires teachers to create student-centered learning and meaningful learning experiences. One of the approaches that supports the implementation of the Merdeka Curriculum is deep learning, which emphasizes deep understanding, critical thinking, and problem-solving skills. This study aims to describe the use of deep learning methods in geography learning within the implementation of the Merdeka Curriculum in senior high schools in West Sumatra. This study employed a descriptive quantitative approach involving 30 geography teachers from the Darek and Pasisia regions of West Sumatra. Data were collected through questionnaires, interviews, and documentation. Data were analyzed using descriptive percentage analysis. The results showed that the use of deep learning methods in geography learning was categorized as ready with a percentage of 75%. Teachers' understanding of deep learning concepts reached 78%, project-based learning implementation reached 76%, and the ability to encourage students' critical thinking reached 79%. The findings indicate that geography teachers have attempted to implement meaningful learning through contextual learning, project-based activities, and environmental phenomena analysis. However, challenges remain in the form of limited learning technology utilization and uneven supporting facilities. Therefore, the use of deep learning methods can support the implementation of the Merdeka Curriculum and improve the quality of geography learning in senior high schools in West Sumatra.